Textile industry consulting report case of CREDITEX S.A.A. - Ramos Alvarado, Janine Estela; Radner, Sandra (Pontificia Universidad Católica del Perú, 2020)
CREDITEX S.A.A. is a company dedicated to the manufacture and sale of yarns, fabrics and garments made with Pima and Tangüis cotton, to both national and international markets. The company is characterized by being vertically integrated, managing its operations in seven plants distributed along the Peruvian coast, thus achieving absolute control during the entire manufacturing process. CREDITEX belongs to the economic group Corporación Cervesur S.A.A., and employs around 1500 people, including operators and administrative staff, as well as a board of Executive Directors composed by six people. In the last five years, the company has shown a decline in sales, which has been notably reflected in the financial statements, for instance, an EBITDA of PEN 12'370 miles was reached in 2018 and PEN 9'171 miles in 2019, indicating a decline of around 25%. This is mainly due to the increase in production costs and it has been possible to demonstrate during the analysis carried out in the present thesis that the costs of materials and labor have had a significant influence on this rise. Hence, the international demand has been reduced as customers have opted for other more economical options. Under this scenario and the prompt need to solve the reduction in sales, it is proposed the strategy of product development for an existing market, which refers to the United States; with a focus on the category of sportswear targeting the premium segment, in addition to the implementation of the FairTrade or Made in Green seal in order to have an added value on the current products and justify their prices. Finally, it is proposed specific recommendations for CREDITEX to improve its internal processes and, consequently, sales and positioning in the local and international markets.

CREDITEX S.A.A. es una empresa dedicada a la manufactura y venta de hilados, tejidos y prendas de algodón tipo Pima y Tangüis; tanto al mercado nacional como internacional. La compañía se caracteriza por ser verticalmente integrada, maneja sus operaciones en siete plantas distribuidas a lo largo de la costa peruana, logrando así tener absoluto control durante todo el proceso de manufactura. CREDITEX pertenece al grupo económico Corporación Cervesur S.A.A., y emplea alrededor de 1500 personas, entre operarios y administrativos, así mismo cuenta con una junta de Directores Ejecutivos conformada por seis personas. En los últimos cinco años, la empresa ha evidenciado reducción en las ventas, lo cual se ha reflejado notablemente en los estados financieros, por ejemplo, se reportó un EBITDA de 12’370 miles de soles en 2018 y 9’171 miles de soles en 2019, lo cual indica una caída de alrededor del 25%. Esto se debe principalmente al incremento en los costos de producción y se ha podido demostrar durante el análisis realizado en la presente tesis que los costos de materiales y mano de obra han tenido bastante influencia en este aumento. De modo que la demanda internacional se ha reducido ya que los clientes han optado por otras opciones más económicas. Bajo este escenario, y la pronta necesidad de resolver la reducción en las ventas, se propone que la empresa opte por la estrategia de desarrollo de producto para un mercado existente, el cual refiere a Estados Unidos; con un enfoque hacia la categoría de ropa deportiva dirigida al segmento premium, además de la implementación del sello FairTrade o Made in Green a fin de tener un valor agregado sobre los productos y sustentar el precio actual. Finalmente, se proponen concretas recomendaciones a fin de que CREDITEX realice mejoras en sus procesos internos y, consecuentemente las ventas y posicionamiento en el mercado local e internacional tengan un mejor comportamiento.
Keywords: Consultores de empresas; industria textil--Estudio de casos; Desarrollo de productos--Planificación; https://purl.org/pe-repo/ocde/ford#5.02.04